Simple derivations in two variables. Issue 9 (2nd September 2019) - Yan, Dan
Abstract: In this article, we study theK -derivation of the form: D = y ∂ x + ( a 2 y 2 + a 1 ( x ) y + a 0 ( x ) ) ∂ y with a 2 ∈ K and a 1 ( x ), a 0 ( x ) ∈ K [ x ] . We show that D is simple if and only if a 0 ( x ) ∈ K * and deg a 1 ( x ) ≥ 1 .